Effects of adolescents' self-efficacy and social anxiety on attitudes toward pros and cons of smoking. (2nd January 2019) - Ayar, Dijle; Bektas, Murat; Bektas, Ilknur; Sal Altan, Sema; Ayar, Ugur
ABSTRACT: This cross-sectional, descriptive research study was conducted in order to examine the impacts of adolescents' levels of social anxiety and self-efficacy on their perceptions of the pros and cons of smoking. Students ( n = 219) in 5th, 6th, 7th, and 8th grades provided demographic details and completed the Middle School Self-Efficacy Scale, the Social Anxiety Scale for Adolescents, and the Decisional Balance Scale. We analyzed the data using Pearson's correlations, multiple regression, and logistic regression. Of the adolescents, 52.8% with a positive perception of smoking were current smokers and 2.2% with a negative perception of smoking were current smokers. Further, 38.9% of females and 61.1% of males perceived that smoking is beneficial to them, whereas 47% of females and 53% of males perceived that smoking cigarette is harmful to them. Adolescents' high self-efficacy, low social anxiety, and mothers' high level of education were associated with perceiving the cons of smoking. Additional experimental studies are needed to increase adolescents' self-efficacy levels, decrease their social anxiety, and teach them life skills. Furthermore, the effects of these precautions on the smoking-related perceptions of adolescents should be examined via experimental studies.